Transnational attention, domestic agenda-setting and international agreement: Modeling necessary and sufficient conditions for media-driven humanitarian interventions; Transnationale Aufmerksamkeit, nationales Agenda-Setting und Internationales Abkommen: Eine Modellierung der notwendigen und hinreichenden Bedingungen für medien-getriebene, humanitäre Interventionen - Julian Junk; Joachim Blatter (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2010)
Interventions based solely or partially on humanitarian grounds are rare; but, over the course of the last two decades, they have become increasingly common phenomena of international politics. Nevertheless international relations theories have thus far not been able to adequately account for their occurrence. The authors present a theoretical framework to explain humanitarian interventions as a result of a multilevel process driven by media attention and political entrepreneurship. They argue that drawing the developed world's public attention to a humanitarian crisis does not suffice to prompt international political reaction to it—it is only a necessary but not a sufficient condition. They therefore develop a consistent, detailed, and falsifiable theoretical model that systematically traces the necessary steps from the spaces of a humanitarian tragedy through the domestic arenas of potentially intervening states to the international arena where agreements on interventions must be reached. The authors take Putnam's two-level game as a template for their model, but they exchange Putnam's interestbased approach with an information-driven approach. The authors examine the structural prerequisites for domestic “windows of recognition,” deduce logical consequences of these “windows of recognition” for the possibility to reach an international agreement to intervene, and describe the functions and roles of peace entrepreneurs who try to overcome structural constraints. – – Ausschließlich bzw. primär humanitär motivierte Interventionen stellen zwar seltene, aber in den letzten zwei Jahrzehnten zunehmend häufiger auftretende Ereignisse dar, die mit den etablierten Theorien der Internationalen Beziehungen nur schwer zu erklären sind. Die Autoren entwickeln in diesem discussion paper ein konsistentes, detailliertes und falsifizierbares theoretisches Modell, das sowohl auf die Möglichkeiten als auch auf die anspruchsvollen Vorraussetzungen für humanitäre Interventionen verweist. Ausgangsthese ist, dass die Aufmerksamkeit der globalisierten Medien eine notwendige, aber keine hinreichende Bedingung für eine humanitäre Intervention darstellt. Im Sinne einer Kausalkette werden weitere Zwischenbedingungen herausarbeitet, die von einer humanitären Tragödie über mediale Aufmerksamkeit und politischem agenda-setting in potentiell intervenierenden Staaten bis hin zu einer internationalen Interventionsentscheidung führen. In Anlehnung an und gleichzeitig in Abgrenzung zu dem interessenbasierten Konzept eines Zwei-Ebenen-Spiels von Putnam wird ein informationszentriertes Modell entwickelt, in welchem das Zusammenspiel von kognitiven Prozessen und normativen Strukturen in transnationalen, nationalen und internationalen Arenen beleuchtet wird. Trotz des informationszentrierten Ansatzes ist das Modell nicht strukturdeterministisch, sondern verweist auf die spezifischen Möglichkeiten von politischen Unternehmern, durch die Verknüpfung von verschiedenen Arenen in diesem Mehrebenenprozess Einfluss zu nehmen..
Keywords: 300